2004
DOI: 10.1097/01.pec.0000113878.10140.36
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Prospective, Multisite Comparison of Pediatric Prehospital Training Methods

Abstract: In this small sample, interactive CD-ROM training shows promise for improving performance. The research design, with additional guards against sample size attrition, may provide a model for multisite EMS education research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…15 The barriers to feasible mass education are many, including the limitations associated with training adult learners, limited access to peer reviewed and tested learning materials, and the ability to provide effective distance instruction. The educational literature is however rich with models that are directed at effective adult learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The barriers to feasible mass education are many, including the limitations associated with training adult learners, limited access to peer reviewed and tested learning materials, and the ability to provide effective distance instruction. The educational literature is however rich with models that are directed at effective adult learning.…”
Section: Discussionmentioning
confidence: 99%
“…The SRL principle is a novel educational methodology based on the spacing effect, the psychological finding that repeated presentations of educational material over spaced intervals increase learning efficiency and improves knowledge retention. 15 Learners were invited to participate in an online electronic SRL module, provided by Qstream, Inc. (www.qstream.com). A question bank for this SRL module was built with 30 multiple choice questions representing variations of the validated testing questions (validation process listed in testing instrument and process), audiovisual aids used during the workshop and descriptive answers.…”
Section: Interventionsmentioning
confidence: 99%
“…Thirteen of the 18 studies showed that TTT programs significantly helped to improve clinical behavior, 8,[15][16][19][20]26 increase knowledge, 22,25,[28][29] or resulted in better patient outcomes. 17 Data contained within the papers and the systematic review authors' interpretation of other information contained within the papers were used to determine the strength of effect of each study. 17 Data contained within the papers and the systematic review authors' interpretation of other information contained within the papers were used to determine the strength of effect of each study.…”
Section: Discussionmentioning
confidence: 99%
“…17,22,[24][25][28][29] All 6 included a preand postintervention measure, and 4 found that a TTT model was effective in improving the knowledge of participants. Six studies assessed effectiveness through knowledge tests.…”
Section: Data Synthesismentioning
confidence: 99%
“…Two studies used an acted-out clinical scenario to assess participants' assimilation of material taught. 12,18 Both were positive. One study used reported practice change and assessed attitude and confidence via questionnaire 13 and did not show a significant effect.…”
Section: Outcome Evaluationmentioning
confidence: 94%